2012
DOI: 10.4319/lo.2012.57.4.1042
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial organic matter support of lake food webs: Evidence from lake metabolism and stable hydrogen isotopes of consumers

Abstract: We quantified the utilization of terrestrial organic matter (OM) in the food web of a humic lake by analyzing the metabolism and the consumers' stable isotopic (C, H, N) composition in benthic and pelagic habitats. Terrestrial OM inputs (3 g C m 22 d 21 ) to the lake greatly exceeded autochthonous OM production (3 mg C m 22 d 21 ) in the lake. Heterotrophic bacterial growth (19 mg C m 22 d 21 ) and community respiration (115 mg C m 22 d 21 ) were high relative to algal photosynthesis and were predominantly (. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
141
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(164 citation statements)
references
References 39 publications
20
141
1
Order By: Relevance
“…Interestingly, our results suggest a lower limit in bacterial biomass allochthony in the order of~70% even in more productive systems where terrestrial DOC becomes more diluted by algal C (Figure 1). These patterns are coherent with previous studies which noted similar high levels of allochthony of bacterial biomass (79% ± 16) across a wide range in lake productivity or color in Québec on the basis of the isotopic composition of bacterial fatty acids (Berggren et al, 2014), as well as in a lake in northern Sweden (480%) (Karlsson et al, 2012) and Selective carbon consumption and allocation F Guillemette et al in two Wisconsin lakes (Kritzberg et al, 2004), although lower estimates have also been reported in the latter (range of 35-70%). Our results are also consistent with a recent hypothesis, suggesting that the rapid transfer and efficient incorporation of compounds exported from soils and leaf litter, or produced via photochemical degradation, may account for a large share of total bacterial production in boreal streams and lakes (up to 80%) (Berggren et al, 2010a, b).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Interestingly, our results suggest a lower limit in bacterial biomass allochthony in the order of~70% even in more productive systems where terrestrial DOC becomes more diluted by algal C (Figure 1). These patterns are coherent with previous studies which noted similar high levels of allochthony of bacterial biomass (79% ± 16) across a wide range in lake productivity or color in Québec on the basis of the isotopic composition of bacterial fatty acids (Berggren et al, 2014), as well as in a lake in northern Sweden (480%) (Karlsson et al, 2012) and Selective carbon consumption and allocation F Guillemette et al in two Wisconsin lakes (Kritzberg et al, 2004), although lower estimates have also been reported in the latter (range of 35-70%). Our results are also consistent with a recent hypothesis, suggesting that the rapid transfer and efficient incorporation of compounds exported from soils and leaf litter, or produced via photochemical degradation, may account for a large share of total bacterial production in boreal streams and lakes (up to 80%) (Berggren et al, 2010a, b).…”
Section: Discussionsupporting
confidence: 80%
“…Here we used previously published values for these parameters, and also a well-established isotopic model (IsoError; Phillips and Gregg, 2001) to account for their variability, but we cannot discard that some methodological biases, isotopic artifacts or secondary C incorporation pathways such as anaplerotic C fixation may have influenced our estimates of allochthony (See Supplementary Note 1 for a discussion of these issues). It should be emphasized that our estimates of bacterial biomass allochthony fall well within the range recently reported in other regions (Kritzberg et al, 2004;Karlsson et al, 2012;Berggren et al, 2014), and that the patterns in BR of terrestrial C also agree with previous reports, that is, that BR in unproductive lakes is dominated by terrestrial C (Karlsson et al, 2007;Karlsson et al, 2008). In addition, it is unlikely that the link that we found between the patterns of allocation of terrestrial versus algal C in the experimental incubations with ambient lake Chl a and phosphorous concentration (both of which being completely unconnected to the actual isotopic or metabolic mass balance), would emerge from chance or methodological bias, providing further evidence that these patterns in bacterial DOC utilization and allocation across lakes that we describe here are real.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The allochthonous contribution generally increases in importance with decreasing light penetration into water (Ask et al 2009, Karlsson et al 2009, Solomon et al 2011), a condition typical of humic lakes. Allochthonous C can support higher trophic levels via a microbial link in pelagic (Jones 1992, Pace et al 2004) and benthic (Premke et al 2010, Karlsson et al 2012) food webs. However, colored allochthonous dissolved organic C (DOC) reduces light availability for phytoplankton and benthic algae, so it also constrains whole-lake primary production and ultimately secondary production (Karlsson et al 2009, Jones et al 2012.…”
mentioning
confidence: 99%